Aktivitas Antioksidan dan Anti-Elastase dari Ekstrak Etanol Tomat (Solanum lycopersicum L.) - Henderson, Alhoi Hendry; Lister, I Nyoman Ehrich; Fachrial, Edy; Girsang, Ermi (Buletin Penelitian Tanaman Rempah dan Obat, 2020)
Skin aging due to the damage caused by ultraviolet radiation and toxic ingredients in cosmetics is still a problem. Tomato has antioxidant and skin protection activities. The study aimed to investigate the potential of tomato as an antioxidant and elastase inhibitor. A 170 g of tomato simplicial powder was extracted using ethanol 70% by the maceration method. Antioxidant activity was measured through 2,2’-Azino-bis 3-ethyl benzothiazoline-6-sulphonic acid (ABTS)-reducing activity. The antiaging activity was measured through anti-elastase activity. Tomato extract (SLE) showed strong ABTS-reducing activity (IC50 = 86.66 ± 10.58) and very strong anti-elastase activity (IC50 = 19.73 ± 0.44). In conclusion, there was a linear correlation between antioxidant activity and anti-elastase activity. However, the antioxidant activity and anti-elastase activity of tomatoes were still below lycopene (IC50 antioxidant = 49.23 ± 2.06 µg.ml-1 and IC50 anti-elastase = 10.39 ± 0.43 49.23 ± 2.06 µg.ml-1). However, it was worth to be developed as a natural product as an antioxidant and anti-elastase.  Further study is required to do fractionation to get the purer lycopene compound from tomato.